Biological Diversity of Carbon Assimilation Among Isolates of the Yeast Dekkera Bruxellensis from Wine and Fuel-Ethanol Industrial Processes - Ganga-Munoz, M (Oxford University Press, 2019)
Dekkera bruxellensis is considered a spoilage yeast in winemaking, brewing and fuel-ethanol production. However, there is growing evidence in the literature of its biotechnological potential. In this work, we surveyed 29 D. bruxellensis isolates from three countries and two different industrial origins (winemaking and fuel-ethanol production) for the metabolization of industrially relevant sugars. The isolates were characterized by the determination of their maximum specific growth rates, and by testing their ability to grow in the presence of 2-deoxy-d-glucose and antimycin A. Great diversity was observed among the isolates, with fuel-ethanol isolates showing overall higher specific growth rates than wine isolates. Preferences for galactose (three wine isolates) and for cellobiose or lactose (some fuel-ethanol isolates) were observed. Fuel-ethanol isolates were less sensitive than wine isolates to glucose catabolite repression (GCR) induction by 2-deoxy-d-glucose. In strictly anaerobic conditions, isolates selected for having high aerobic growth rates were able to ferment glucose, sucrose and cellobiose at fairly high rates without supplementation of casamino acids or yeast extract in the culture medium. The phenotypic diversity found among wine and fuel-ethanol isolates suggests adaptation to these environments. A possible application of some of the GCR-insensitive, fast-growing isolates in industrial processes requiring co-assimilation of different sugars is considered. © 2019 FEMS.